Implementing Supported Self-Management in Community-Based Stroke Care: A Secondary Analysis of Nurses’ Perspectives - Kidd, Lisa (J Clin Med, 2020)
The provision of supported self-management (SSM) is recommended in contemporary guidelines to address the longer-term needs and outcomes of stroke survivors and their families, yet its implementation across stroke pathways has been inconsistent. This paper presents a secondary analysis of qualitative data, which aims to identify and offer insight into the challenges of implementing SSM from the perspectives of community stroke nurses (n = 14). The findings revealed that the implementation of SSM in stroke is influenced by factors operating at multiple levels of the healthcare system. Contextual challenges arise because of different understandings and interpretations of what SSM is, what it comprises and professionals’ perceptions of their roles in its implementation in practice. A professionally controlled, one-size-fits-all model of SSM continues to be reinforced within organizations, offering few opportunities for nurses to deliver contextually tailored and person-centred SSM. In conclusion, there are many professional concerns and organizational tensions that need to be addressed across multiple layers of the healthcare system to achieve the consistent implementation of contextually tailored and person-centred SSM following a stroke. Attempts to address these challenges will help to narrow the gap between policy and practice of implementing SSM, ensuring that stroke survivors and families benefit from SSM in the longer-term.